2013
DOI: 10.1002/14651858.cd003260.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training and cognitive rehabilitation for mild to moderate Alzheimer's disease and vascular dementia

Abstract: Cognitive training and cognitive rehabilitation for mild to moderate Alzheimer's disease and vascular dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
286
2
26

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(321 citation statements)
references
References 115 publications
7
286
2
26
Order By: Relevance
“…Of the five cognitive measurements used, the ANOVA test confirmed an effect of the training for three subtests: training gain effects were observed immediately after the intervention for attention and processing speed tasks related to codes [F(1)=5. 40 Concerning the similarities between the results of the present study and those found in international literature, consonance was observed with the results of the longitudinal project known as ACTIVE (Advanced Cognitive Training for Independent and Vital Elderly), 11,30 which reported an increase in cognitive performance immediately after training among participants who received training for attention and processing speed. Conversely, intervention effects were obtained for episodic memory and reasoning tasks.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Of the five cognitive measurements used, the ANOVA test confirmed an effect of the training for three subtests: training gain effects were observed immediately after the intervention for attention and processing speed tasks related to codes [F(1)=5. 40 Concerning the similarities between the results of the present study and those found in international literature, consonance was observed with the results of the longitudinal project known as ACTIVE (Advanced Cognitive Training for Independent and Vital Elderly), 11,30 which reported an increase in cognitive performance immediately after training among participants who received training for attention and processing speed. Conversely, intervention effects were obtained for episodic memory and reasoning tasks.…”
Section: Discussionsupporting
confidence: 89%
“…[6][7][8][9][10] There is also evidence of the positive impact of these interventions on the performance of elderly individuals with accentuated mental decline due to dementia, suggesting the possibility of assuaging and/or delaying cognitive impairment, although the scope of the interventions is more limited when compared with non-clinical groups. [11][12][13] There is some confusion about the terms commonly used to define the different types of cognitive interventions for the elderly. 14,15 Literature contains several different terms to describe intervention techniques, of which the most common are cognitive stimulation, cognitive training and cognitive rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consist ent wit h t he exist ing weak evidence f or such int ervent ions in dement ia (Bahar-Fuchs, Clare, & Woods, 2013). It is possible t hat guided hierarchical search wit h ext ernal support could f acilit at e t he generat ive ret rieval process in t hose wit h weaker semant ic f luency, t hus scaf f olding semant ic search, and pot ent ially increasing t he episodic cont ent of AM relat ive t o what would occur ot herwise.…”
Section: Discussionmentioning
confidence: 56%
“…Na literatura internacional, as modalidades mais comuns de intervenção cognitiva parecem caminhar para um consenso taxonômico (Bahar-Fuchs, Clare, & Woods, 2013), delimitando três tipos principais: (a) estimulação mental, que geralmente envolve a realização e a prática repetida de tarefas cognitivas padronizadas; (b) treino cognitivo, que engloba tarefas de estimulação mental, mas avança em termos de esforço de aprendizagem ao focar no ensino de estratégias cognitivas para potencializar os efeitos da intervenção (Bruschet et al, 2003;Clare & Woods, 2004); e (c) reabilitação cognitiva, conhecida também como abordagem individualizada, em que se atinge, uma de cada vez, deficiências específicas na vida cotidiana, em vez de melhorar o desempenho em tarefas cognitivas particulares (Clare, Woods, Cook, Orrell, & Spector, 2003;Clare & Woods, 2004). Essas abordagens são complementares, sendo que a escolha de um tipo particular depende dos objetivos da melhoria ou manutenção cognitiva e do perfil cognitivo da população-alvo (Burschet et al, 2010).…”
Section: Introductionunclassified